The Motivation to Adopt E-commerce Among Malaysian Entrepreneurs - Koe , Wei-Loon; Afiqah Sakir, Nurul (Organizations and Markets in Emerging Economies, 2020)
E-commerce is important in creating a knowledge society and cashless business environment in the era of the fourth industrial revolution (IR 4.0). However, not all Malaysian entrepreneurs are ready for this digital way of performing business. The e-commerce ecosystem is still less matured, and the e-commerce adoption rate is still low among entrepreneurs of small and medium enterprises (SMEs). Therefore, this study was conducted to determine the factors that influence the entrepreneurs’ motivation to adopt e-commerce. Self-determination theory (SDT) was employed in determining the factors that influence the motivation to adopt e-commerce. This study employed a quantitative research method and surveyed 273 entrepreneurs through self-administered questionnaires. It used multiple regressions analysis to analyse the data and test the hypotheses. Based on the results obtained, it concluded that competence, relatedness and autonomy positively and significantly influenced entrepreneurs’ motivation to adopt e-commerce. Relatedness was found to be the most important factor, followed by autonomy and competence. This study contributed to entrepreneurship literature by applying SDT in understanding entrepreneurs’ motivation in e-commerce adoption. It also shed light on the importance of individual psychological factors in decision making among entrepreneurs. The study suggested that building a strong connection among the entrepreneurs, providing freedom to business operations and developing knowledgeable entrepreneurs are some crucial steps in motivating entrepreneurs to adopt e-commerce, especially in a developing country like Malaysia.